2009
DOI: 10.1596/1813-9450-4901
|View full text |Cite
|
Sign up to set email alerts
|

Sea-Level Rise And Storm Surges: A Comparative Analysis Of Impacts In Developing Countries

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 13 publications
0
56
0
Order By: Relevance
“…Using six indicators, Dasgupta et al (2009) [7] assess the impact of SLR on 84 coastal developing countries. Considering the use of land, population, gross domestic product, urban extent, agricultural extent and impacted wetlands, they demonstrate that Vietnam, with one meter of SLR, ranks among the top five most-impacted countries [7]. Additionally, the World Bank [8] ranks Vietnam among the 12 World Bank client countries most at risk from sea level rise due to climate change.…”
Section: Coastal Flooding In the Red River Deltamentioning
confidence: 99%
“…Using six indicators, Dasgupta et al (2009) [7] assess the impact of SLR on 84 coastal developing countries. Considering the use of land, population, gross domestic product, urban extent, agricultural extent and impacted wetlands, they demonstrate that Vietnam, with one meter of SLR, ranks among the top five most-impacted countries [7]. Additionally, the World Bank [8] ranks Vietnam among the 12 World Bank client countries most at risk from sea level rise due to climate change.…”
Section: Coastal Flooding In the Red River Deltamentioning
confidence: 99%
“…The generalized assumption is that dwellings located in higher grounds are less likely to be affected by storm surges [47]. After analysing the DEM, it was found that the average elevation of the dwellings is only 3.5 m [46].…”
Section: Pre-event Situationmentioning
confidence: 99%
“…To be specific, four Philippine cities -San Jose, Manila, Roxas, and Cotabato -are among the top 10 cities in the East Asia/Pacific region most vulnerable to the climate-related impacts of intensified storm surges and sea-level rise [Dasgupta et al, 2009].…”
Section: Indicators On the Impact On The Environment And Climatementioning
confidence: 99%